Robust and Multifunctional Kirigami Electronics with a Tough and Permeable Aramid Nanofiber Framework. Issue 50 (10th November 2022) - Liu, Hongzhen; Li, Hegeng; Wang, Zuochen; Wei, Xi; Zhu, Hengjia; Sun, Mingze; Lin, Yuan; Xu, Lizhi
Abstract: Kirigami designs are advantageous for the construction of wearable electronics due to their high stretchability and conformability on the 3D dynamic surfaces of the skin. However, suitable materials technologies that enable robust kirigami devices with desired functionality for skin‐interfaces remain limited. Here, a versatile materials platform based on a composite nanofiber framework (CNFF) is exploited for the engineering of wearable kirigami electronics. The self‐assembled fibrillar network involving aramid nanofibers and poly(vinyl alcohol) combines high toughness, permeability, and manufacturability, which are desirable for the fabrication of hybrid devices. Multiscale simulations are conducted to explain the high fracture resistance of the CNFF‐based kirigami structures and provide essential guidance for the design, which can be further generalized to other kirigami devices. Various microelectronic sensors and electroactive polymers are integrated onto a CNFF‐based materials platform to achieve electrocardiogram (ECG), electromyogram (EMG), skin‐temperature measurements, and measurement of other physiological parameters. These mechanically robust, multifunctional, lightweight, and biocompatible kirigami devices can shed new insights for the development of advanced wearable systems and human–machine interfaces. Abstract : Designing robust and multifunctional kirigami electronics for wearable applications imposes strict restrictions on the constituent materials. In this work, a versatile materials platform based on a composite nanofiber framework (CNFF) is exploited for the engineering of wearable kirigami electronics. Various microelectronic sensors and electroactive polymers are integrated onto the CNFF‐based materials platform to achieve measurements of physiological parameters.